Ideologies underpinning the Indonesian National Qualification Framework (IQF) for higher education website text - Yuwono, Untung (Universitas Pendidikan Indonesia, 2019)
Political and economic globalization has influenced the education sector. A significant component of education is the process of facilitating studentsâ€™ acquisition of competence and values to enter the job market. The standard of competence at every level of education thus becomes the benchmark for the accurate estimation of a personâ€™s success in the job market. Indonesia was not left behind in this trend, and the concept of the National Qualification Framework came into being. The first milestone occurred in 2012 when the Kerangka Kualifikasi Nasional Indonesia (Indonesian National Qualification Framework [IQF]) began to be enforced by the government of Indonesia, and the planning and implementing phases of IQF were conducted. One of these phases is the socialization and dissemination of information on the IQF in higher education through a website (kkni-kemenristekdikti.org) hereafter called the IQF website.Â This paper qualitatively and quantitatively examines the ideas outlined in the IQF website text using critical discourse analysis framework. Through the textual analysis using systemic functional linguistics, this paper identifies the values highlighted by the IQF and shows that IQF is closely related to the working world. The word kerja (work/job), which appears throughout the text, collocates to words that manifest actors, institutions, processes, products, and values, and its use suggests that it is intended as the primary objective of the IQF. The textual analysis reveals that the context of neoliberalism and work within the workforce has become the trigger for change in national education in Indonesia. The purpose of higher education is now based on global pragmatism, that is, to provide students with competence in accordance with the needs of the job market, and, as a result, all educational regulations are directed to meet the demands of the job market, which ultimately shape the goals and competence levels of the IQF.